BLOCKCHAIN AND ARTIFICIAL INTELLIGENCE AS TOOLS OF ECONOMIC STRATEGY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes modern vectors of application of blockchain technologies and artificial intelligence (AI) in the process of formation and implementation of economic strategy. The role of these technologies in increasing the transparency of financial transactions, optimizing business processes and developing sustainable growth models is emphasized. Particular attention is paid to the issues of integration of blockchain and AI in such areas as management, logistics, healthcare and digital finance.